Genetic determinants of head and neck cancer: exploring causality among immune cells and plasma metabolites through two-sample Mendelian randomization and mediation analysis - Yuting Lu; Xiangnan Du; Hanlin Liu; Qing He; Xiaolin Cao (Discover Oncology)
Abstract Background Head and neck cancer represents a major health challenge worldwide, characterized by frequent late-stage diagnoses that adversely affect treatment success. The immune system’s cellular components significantly influence the initiation, advancement, and outcome of head and neck malignancies. Methods Our investigation employed Mendelian randomization techniques to analyze genome-wide association data encompassing 731 immune cell phenotypes, 1400 plasma metabolites, and 2281 head and neck cancer patients. We utilized mediation analysis to assess how plasma metabolites might serve as intermediaries between immune cells and head and neck cancer development. We evaluated heterogeneity using IVW and MR-Egger approaches, examined pleiotropy through MR-Egger intercepts, and conducted sensitivity testing via the leave-one-out methodology. Results Our analysis revealed potential causal connections linking three immune cell phenotypes and twelve plasma metabolites to head and neck cancer. Through mediation Mendelian randomization, we identified that 3-hydroxypyridine glucuronide concentrations function as a mediator between CD3 on CD39 + secreting Treg cells and head and neck cancer. The measured mediating effect was − 0.011, 95%CI (-0.02, -0.002), representing a mediating proportion of 9.27%. Additionally, we also found that CD3 on CD39 + secreting Treg mediated Cortolone glucuronide (1) levels and CD80 on granulocyte mediated 3-amino-2-piperidone levels exhibit the masking effect on head and neck cancer. Conclusions These discoveries provide fresh perspectives on the intricate interactions occurring within the tumor microenvironment and may highlight potential targets for reducing head and neck cancer risk.